THE FUNCTIONAL PROPERTIES OF CHEMICALLY AND ENZYMATICALLY MODIFIED WHEAT GLUTEN - A. Shuaib Jasim; J. M. Nasser (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was carried out to investigate the effect of chemically (using L-Cysteine) and enzymatically (by papain) modification on the functional properties of hard wheat gluten. The modification process is run by both methods individually and synergistically. The results showed an increase in the degree of hydrolysis (DH) of lyophilized wheat gluten upon adding the reducing agent at different concentrations (50, 100, 150, 200, 250 ppm). The values for (DH) were (5.29, 6.18, 6.22, 6.26, and 7.48%) respectively. While for papain (2000 units / g protein) those values were (10.25, 12.71, 13.54, 13.88, 15.62%) respectively when the reducing agent (same concentration above) and papain were used synergistically. The functional properties (water holding capacity, emulsifying ability and stability, foam formation and stability, protein solubility, and oil holding capacity) of the gluten under study were examined. The results showed that the enzymatic modification significantly improved the functional properties of the experimental proteins compared to the reducing agent modification.